2011
DOI: 10.1111/j.1530-0277.2011.01444.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Verbal Learning and Memory in Children With Heavy Prenatal Alcohol Exposure or Attention‐Deficit/Hyperactivity Disorder

Abstract: Background Children with fetal alcohol spectrum disorders (FASD) have deficits in verbal learning and recall. However, the specificity of these deficits has not been adequately tested. In the current study, verbal learning and memory performance of children with heavy prenatal alcohol exposure was compared to children with attention-deficit/hyperactivity disorder (ADHD), a disorder commonly seen in alcohol-exposed children. Methods Performance on the California Verbal Learning Test – Children's Version (CVLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 65 publications
6
57
0
2
Order By: Relevance
“…Studies have shown that children with PAE have deficits encoding verbal information [33][34][35][36][37]. Children with weaknesses encoding language may display problems following multistep directions or classroom discussions.…”
Section: Fasd and Language And Social Skill Deficitsmentioning
confidence: 99%
“…Studies have shown that children with PAE have deficits encoding verbal information [33][34][35][36][37]. Children with weaknesses encoding language may display problems following multistep directions or classroom discussions.…”
Section: Fasd and Language And Social Skill Deficitsmentioning
confidence: 99%
“…Research indicates that children's memory functioning 50 PHYSICAL DISABILITIES: EDUCATION AND RELATED SERVICES varies according to the degree of prenatal alcohol exposure. For example, children with moderate prenatal alcohol exposure have demonstrated deficits in short-term and long-term memory , while children with heavy prenatal alcohol exposure have exhibited poor recognition and retention of information previously taught (Crocker et al, 2011).…”
Section: Physical Disabilities: Education and Related Servicesmentioning
confidence: 99%
“…Individuals with FASD experience deficits in both the quantity and the quality of the information they process (Burden et al, 2009;. When presented with the same number and type of learning opportunities, children with FASD are likely to learn less information than children without prenatal alcohol exposure Roebuck-Spencer & Mattson, 2004), as well as those with Attention Deficit Hyperactivity Disorder (ADHD) (Crocker, Vaurio, Riley, & Mattson, 2011). Further, when increasing amounts of visual stimuli are provided, a significant positive linear effect is EDUCATING INDIVIDUALS WITH FASD 49 observed for children with FASD in the quantity of time required to process the growing amounts of information .…”
mentioning
confidence: 99%
“…Research indicates that children's memory functioning varies according to the degree of prenatal alcohol exposure. For example, children with moderate prenatal alcohol exposure have demonstrated deficits in short-term and long-term memory (Willford et al, 2004), while children with heavy prenatal alcohol exposure have exhibited poor recognition and retention of information previously taught (Crocker et al, 2011).…”
Section: Cognitive Developmentmentioning
confidence: 99%
“…Individuals with FASD experience deficits in both the quantity and the quality of the information they process (Burden et al, 2009;. When presented with the same number and type of learning opportunities, children with FASD are likely to learn less information than children without prenatal alcohol exposure (Mattson & Roebuck, 2002;Roebuck-Spencer & Mattson, 2004), as well as those with Attention Deficit Hyperactivity Disorder (ADHD) (Crocker, Vaurio, Riley, & Mattson, 2011). Further, when increasing amounts of visual stimuli are provided, a significant positive linear effect is observed for children with FASD in the quantity of time required to process the growing amounts of information (Simmons, Thomas, Levy, & Riley, 2006).…”
Section: Cognitive Developmentmentioning
confidence: 99%